Pengaruh Profitabilitas, Ukuran Perusahaan dan Tarif Pajak terhadap Struktur Modal (Studi Perusahaan Sektor Pertambangan di Bursa Efek Indonesia Tahun 2019-2022) - Dimas Cahya Aji (Universitas Sains dan Teknologi Komputer, 2023)
ABSTRACT This research delves into theipinfluenceipof profitability, ipcompanyipsize, ipand iptax rates on the capitalipstructure of mining sectoripcompanies listedipon the Indonesian Stock Exchange between 2019 and 2022. The sample selection involved the purposive sampling method, yielding 112 samples for analysis. Theipfindingsiprevealithat profitability and firmisize significantly affectitheicapital structure,iwhile tax rates do not exhibit a significant impact. Data collection was performed quantitatively, and multipleislinearisregression analysis was employed for data processing. The financial reports used for analysis were obtained from theiIndonesiaiStockiExchange via the idx.co.id website and processed using SPSS